Pomen žrtvovanja živali - Dolinar, Maja (Etnolog. Nova vrsta (Ljubljana), 2013)
Eid-Al-Adha, or to use the in Slovenia more familiar name Kurban Bayram, is a Muslim holiday celebrated at the end of the annual Hajj - the pilgrimage to Mecca. The feast is a reminder of Abraham's willingness to sacrifice his first-born son Ismail as an act of submission to god. Muslims honour this day with prayers and religious sacrifices of animals, and it is therefore also called the Žfeast of the sacrificeŽ. The article is based on an ethnographic description of celebrating the holiday with a Moroccan family and reveals the meaning of religious sacrifice of animals to Muslims in contemporary Morocco.
Keywords: ethnology; etnologija; anthropology; antropologija; Maroko; ljudska verovanja; ljudski prazniki; kurban bajram; obredi